2011
DOI: 10.1111/j.1526-100x.2010.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Road Culverts on Nekton in New England Salt Marshes: Implications for Tidal Restoration

Abstract: In recent years, salt marsh restoration projects have focused upon restoring hydrology through culvert enlargement to return functional values lost due to reduced tidal flow. To evaluate culvert effects on upstream nekton assemblages, fyke nets were set upstream of tidally restricted creeks, creeks recently restored with larger culverts, and paired reference creeks in New Hampshire and Maine, U.S.A. Subtidal habitats created or enlarged by scour were found immediately upstream of undersized culverts. All marsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Decreased prey diversity, and subsequently the loss of trophic levels have been documented in tidally restricted mangrove systems (Layman et al 2007). Furthermore, decreased movement of important prey species (e.g., F. heteroclitus, C. septemspinosa) between upstream and downstream regions of tidally restricted marshes (Eberhardt et al 2011) may result in a loss of prey resources for A. rostrata in some marsh areas. As a result, the observed lower trophic position of eels in highly restricted systems may indicate an altered trophic structure in marshes subject to reduced tidal flushing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased prey diversity, and subsequently the loss of trophic levels have been documented in tidally restricted mangrove systems (Layman et al 2007). Furthermore, decreased movement of important prey species (e.g., F. heteroclitus, C. septemspinosa) between upstream and downstream regions of tidally restricted marshes (Eberhardt et al 2011) may result in a loss of prey resources for A. rostrata in some marsh areas. As a result, the observed lower trophic position of eels in highly restricted systems may indicate an altered trophic structure in marshes subject to reduced tidal flushing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, A. rostrata are frequently captured in New England salt marsh habitats (e.g., Dionne et al 1999;Eberhardt et al 2011;Nixon and Oviatt 1973) and in some studies were found to comprise the majority of fish biomass . Despite the abundance of A. rostrata in northeast salt marshes, little is known about their use of these habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreases in bird species richness, density, and abundance were documented in restricted marshes [36], [38], but nekton response was variable across studies, with density, abundance, and species richness varying by site and species [25], [36], [37], [39], [40]. Tidally restored sites exhibit wide variation in support of nekton for several years post-restoration while hydrologic, environmental, and physical variables respond over time to increased tidal flooding and duration [25], [36], [41], [42].…”
Section: Introductionmentioning
confidence: 99%
“…Her efforts also went into garnering a trust that provides funds for a post-doctoral fellow to perform high-level research in conservation ecology. Michele, her students, and post-doctoral fellows performed a variety of research activities that included studying the utilization of marsh ecosystems by fish (Dionne et al 1999;MacKenzie and Dionne 2008), coastal restoration (Burdick and Dionne 1994;Burdick et al 1997;Koniski et al 2006), assessing human and climate threats on coastal systems (Chen et al 2009;Crain et al 2009;Dijkstra et al 2013;Eberhardt et al 2011), and investigating species-specific interactions in marsh ecosystems (Dijkstra et al 2012;Tyrrell et al 2012). She was a proponent of long-term monitoring that could provide effective baseline data sets to determine the conditions of these ecosystems (Neckles and Dionne 2000).…”
mentioning
confidence: 99%